Sosialisasi Komunikasi Informasi dan Edukasi Daerah Rawan Bencana di SMP Negeri 2 Meureubo, Kabupaten Aceh Barat - Rita Fazlina; Raina Parmitalia Dinda; Fadli Idris; Fachruddin Fachruddin; Astiah Amir; Veranita Veranita; Dewi Purnama Sari; Rezqi Malia; Dian Febrianti; Teuku Farizal; Alvisyahri Alvisyahri; Rinaldy Rinaldy; Zulyaden Zulyaden; Roni Agusmaniza; Aulia Rahman; Andi Yusra; Delfian Masrura (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2024)
The Socialization of Communication, Information, and Education (KIE) for Disaster-Prone Areas in Aceh Barat Regency in 2024 aims to enhance public understanding and preparedness for various natural disasters, such as fires, earthquakes, and tsunamis. This activity is a collaboration between the Regional Disaster Management Agency (BPBD) of Aceh Barat and the Civil Engineering Department lecturers from the Faculty of Engineering, Universitas Teuku Umar. The socialization took place at SMP Negeri 2 Meureubo, with students as the main participants. The program included educational presentations about the risks and mitigation measures for different types of disasters and concluded with an earthquake simulation. The students participated enthusiastically, showing an intense interest in understanding how to protect themselves and respond correctly during a disaster. The earthquake simulation provided participants with the opportunity to practice their ability to react to emergency situations directly. The results of the activity demonstrated an increase in students' awareness and understanding of the importance of disaster preparedness. It is hoped that this program will be continuously implemented in other schools across Aceh Barat to help build a more resilient community in facing future disaster threats.